A STUDY ON THE PRESCRIBING PATTERN OF ANTIMICOBIAL DRUGS IN PATIENTS ATTENDING THE EAR, NOSE, THROAT DEPARTMENT OF A TERTIARY CARE TEACHING HOSPITAL - PHUKAN, SWOPNA; DAS, SAHELI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the study is to evaluate the prescription pattern of antimicrobial drugs in the department of ear, nose, throat (ENT) of a tertiary care teaching hospital in Guwahati. Methods: The present study was conducted in the department of ENT after getting approval from the Institutional Ethics Committee (No MC/190/2007/Pt – 11 December -18/18). It was a prospective observational study for a period of 6 months. Prescriptions were collected from the outdoor and indoor patients of ENT. Results: In the present study, the majority of the patients were male (64.1%). Mostly, the patients belonged to the age group of 31–60 years (52%). Pharyngitis (20.8%) was the most commonly encountered disease which was reported followed by ear discharge (16.2%) and acute suppurative otitis media (15.8%). Total number of antimicrobial drugs prescribed for 240 patients was 303, amoxicillin-clavulanic acid being the most common (66%). About 89.4% of the drugs were included in the WHO Model List of Essential Medicines, 2019. Majority of the patients were prescribed only one drug. Conclusion: The drug prescribed commonly for ENT infections was amoxicillin-clavulanic acid combination. Around 71.6% of drugs were prescribed by their brand names. Intervention is needed to promote the use of generic drugs as these drugs are with the same composition and provide the same therapeutic benefit at reasonable price.